Influence of water on deformation and failure of gypsum rock. (October 2022) - Caselle, C.; Baud, P.; Kushnir, A.R.L.; Reuschlé, T.; Bonetto, S.M.R.
Abstract: While water is known to significantly reduce the strength of rocks, there remains a paucity of data on water-weakening of gypsum. Here, we quantify water-weakening in a natural gypsum facies from Monferrato (Italy) by performing experiments on nominally dry, oil-saturated, and water-saturated samples. Uniaxial and conventional triaxial experiments revealed significant water-weakening in Monferrato gypsum as well as a strong strain-rate dependence of uniaxial compressive strength. Moreover, uniaxial creep tests showed significant time-dependent deformation in samples saturated with sulphate over-saturated water, but not in dry and oil-saturated samples. The creep phenomenology is similar to that observed in other rock types and is consistent with stress-corrosion microcracking, which is supported by our microstructural observations. However, we systematically recorded more inelastic strain in samples deformed at low strain-rates suggesting that additional mechanisms were also active. Comparing our new data on short-term strength with published results for other rock types, we conclude that, when saturated with water in equilibrium with the rock, weakening in gypsum is not notably higher than in other rocks and is partially due to a reduction of fracture toughness in the presence of water.